AIRLINE CABIN AIR NOT HEALTH BUT VENTILATION ISSUE (Tufts Archival Research Center, 2007)
Marginalia; Report prepared for various presses claiming that airline cabin air is not a health but a ventilation issue. Maintains that high concentrations of carbon dioxide due to poor ventilation systems are to blame for negative health effects of cabin air. States that there was no health justification for banning on-board smoking. Emphasizes that nicotine concentrations found were well below the safety limits applied in working environments.